Prevalence of HBV genotypes in South American immigrants affected by HBV-related chronic active hepatitis - Palumbo,Emilio (2007)
This study evaluated the prevalence of HBV infection in a population of South American immigrants in Italy and to determine in patients with detectable serum HBV-DNA the HBVgenotypes. Between April 2005 and April 2006 a total of 130 South American immigrants were tested for HBsAg. In HBsAg positive patients the biochemical and virological activity of infection and the possible presence of co-infections (HCV, HDV, HIV) were evaluated. In patients with detectable serum HBV DNA, the HBV genotype was determined by INNOLiPA. Among the 130 subjects tested, 14 (10.7%) resulted HBsAg positive. All were men, with a mean age of 22 years (range 19-37) and 12 (85.7 %) came from Brazil, while 2 (14.3%) came from Ecuador. All patients infected by HBV had elevated alanine-aminotransferase serum levels (mean level was 127 IU/L, range 74-312) and serum HBV DNA detectable by PCR-Real Time (mean level 1,037,652 copies/mL, range 19,876-1,377,648). Genotype distribution was as follow: genotype D, 9 (64.2%), genotype A, 5 (35.8%). All patients infected by genotype D came from Brazil, while among the patients infected by genotype A, three came from Brazil and two from Ecuador. Our study evidences a moderate prevalence of HBV-infection in South American immigrants with the identification of two genotypes, D and A. These genotypes are not the most prevalent in the South America and this is probably the expression of a possible geographical redistribution of HBV genotypes.